Understanding the impact of diverse structural properties of homogalacturonan rich citrus pectin-derived compounds on their emulsifying and emulsion stabilizing potential. (April 2022) - Humerez-Flores, Jessika N.; Verkempinck, Sarah H.E.; De Bie, Margot; Kyomugasho, Clare; Van Loey, Ann M.; Moldenaers, Paula; Hendrickx, Marc E.
Abstract: The emulsifying and emulsion stabilizing potential of 13 citrus pectin (CP) derived samples exhibiting differences in degree of methylesterification (DM, 11–74%) and molecular weight (Mw, 2.5–151 kDa) was studied using an integrated multimethod approach, which involved the evaluation of structural and physicochemical properties of each pectin sample, as well as detailed storage stability studies of pectin-containing emulsions. It was observed that all CP derived samples had a high negative ζ-potential, depending on the DM of the sample and pH of the medium. Furthermore, they exhibited an enhanced interfacial activity at pH 6.0 compared to pH 2.5. Moreover, significant differences in viscosity were observed between CP derived samples of high (> 62 kDa) and low (< 62 kDa) Mw . A storage experiment was performed for 14 days at 4 °C to determine the physical stability of 26 oil-in-water emulsions (pH 2.5 versus 6.0) containing the CP derived pectin samples. The results revealed greater stability for high Mw (> 62 kDa) CP containing emulsions at pH 2.5, regardless pectin DM. On the contrary, flocculation and coalescence were observed at early stages in the 20 low Mw CP containing emulsions, indicating destabilization. Likewise, creaming and phase separation of the latter emulsions was evident from the day of emulsion preparation. Generally, low Mw (< 62 kDa) CP compounds performed poorly when applied as sole stabilizing compound in the emulsions. Graphical abstract: Image 1 Highlights: Low Mw (<62 kDa) homogalacturonan-rich citrus pectin samples exhibited decreased emulsifying capacity as compared to the pectin materials with Mw  > 100 kDa. Differences in viscosity increasing capacity among the different pectin materials is suggested to be the main factor influencing the stability of the formulated emulsions. Coalescence and flocculation were considered the main destabilizing mechanisms in the emulsions formulated with the low Mw pectin materials. The DM of high Mw (>100 kDa) pectin samples had a minor effect on the emulsifying properties.